Age, Comorbid Conditions, and Racial Disparities in COVID-19 Outcomes - Wiley, Zanthia (J Racial Ethn Health Disparities, 2021)
BACKGROUND: Black patients are disproportionately affected by COVID-19. The purpose of this study was to compare risks of hospitalization of Black and non-Black COVID-19 patients presenting to the emergency department and, of those hospitalized, to compare mortality and acute kidney injury. METHODS: A retrospective cohort of 831 adult COVID-19 patients (68.5% Black) who presented to the emergency departments of four academic hospitals, March 1, 2020–May 31, 2020. The primary outcome was risk of hospitalization among Blacks vs. non-Blacks. Secondary outcomes were mortality and acute kidney injury, among hospitalized patients. RESULTS: The crude odds of hospitalization were not different in Black vs. non-Black patients; however, with adjustment for age, Blacks had 55% higher odds of hospitalization. Mortality differed most in the model adjusted for age alone. Acute kidney injury was more common in the Black hospitalized patients, regardless of adjustment. Stratified analyses suggested that disparities in the risk of hospitalization and of in-hospital acute kidney injury were highest in the youngest patients. CONCLUSIONS: Our report shows that Black and non-Black patients presenting to the emergency department with COVID-19 had similar risks of hospitalization and, of those who were hospitalized, similar mortality when adjusted for multiple factors. Blacks had higher risk of acute kidney injury. Our results suggest that examination of disparities without exploration of the individual effects of age and comorbidities may mask important patterns. While stratified analyses suggest that disparities in outcomes may differ substantially by age and comorbid conditions, further exploration among these important subgroups is needed to better target interventions to reduce disparities in COVID-19 clinical outcomes.